The Use of Poster Media to Enhance Student Learning Outcomes in Descriptive Text Writing - Jannah, Raudhatul; Fona , Zahara; Fakhriah, Fakhriah; Khaira , Niswatul (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2022)
This research reported observations regarding students' learning activities. The results of the study revealed that most students did not enjoy the learning process and yet become passive learners. This can be driven by several aspects, particularly the employment of conventional methods by teachers during the class, and the media exploited was not engaging. Thus, this study proposed a resolution to construct learning activities more engaged. This study suggested that the application of poster media can be an alternative to enhance students' learning outcomes in Writing Descriptive Text topic, particularly at the junior high school (SMPN 1). The data sources in this study were seventh-grade students of SMPN 1 Darul Aman (The academic year 2021/2022). Data compiled from students comprise data on the results of written tests carried out at the end of each cycle, non-tests, including observation sheets, and interviews. The data were analyzed using qualitative descriptive analysis.